Determinación del índice trófico de la calidad de agua a partir de la presencia de diatomeas epilíticas en el río Cutuchi sector Parque Nacional Cotopaxi, cantón Latacunga - Chasiquiza Cando, Myriam Sofía (2017)
The objective of this study was to determine the trophic index of water quality and the presence of epilithic diatoms in the Cutuchi River in the section located in the Cotopaxi National Park Sector. In this place there were established 6 points and 7 samples were carried out on different dates during the months of October, November and December, obtaining a total of 42 samples. Furthermore, 2 water samples were collected in January in order to determine the physicochemical and microbiological characteristics of the area and the degree of eutrophication.In order to calculate the trophic state of the river stretch, the Trophic State Index (EIT) proposed by Carlson (1977) was used, where the total phosphorus value was used. From the taxonomic study of the collected samples, 55 species of epilitic diatoms were identified, the most representative group where the Cocconeis placentula with 58 individuals. The average value of the EIT established that the water quality in this sector shows mesotrophic state, which was related to the community of epilitic diatoms found.The results of the physicochemical and microbiological analyzes provide an additional information of the water quality in the study area.The results obtained will be the basis for new researchs based on epilitic diatoms and the trophic index in the Cutuchi River, with this information it will be possible to determine epilitic diatoms as bioindicators of water quality.